The sugar code: letters and vocabulary, writers, editors and readers and biosignificance of functional glycan–lectin pairing - Kaltner, Herbert; Abad-Rodríguez, José; Corfield, Anthony P.; Kopitz, Jürgen; Gabius, Hans-Joachim (Biochemical journal, 2019)
Abstract. Ubiquitous occurrence in Nature, abundant presence at strategically important places such as the cell surface and dynamic shifts in their profile by diverse molecular switches qualifies the glycans to serve as versatile biochemical signals. However, their exceptional structural complexity often prevents one noting how simple the rules of objective-driven assembly of glycan-encoded messages are. This review is intended to provide a tutorial for a broad readership. The principles of why carbohydrates meet all demands to be the coding section of an information transfer system, and this at unsurpassed high density, are explained. Despite appearing to be a random assortment of sugars and their substitutions, seemingly subtle structural variations in glycan chains by a sophisticated enzymatic machinery have emerged to account for their specific biological meaning. Acting as ‘readers’ of glycan-encoded information, carbohydrate-specific receptors (lectins) are a means to turn the glycans’ potential to serve as signals into a multitude of (patho)physiologically relevant responses. Once the far-reaching significance of this type of functional pairing has become clear, the various modes of spatial presentation of glycans and of carbohydrate recognition domains in lectins can be explored and rationalized. These discoveries are continuously revealing the intricacies of mutually adaptable routes to achieve essential selectivity and specificity. Equipped with these insights, readers will gain a fundamental understanding why carbohydrates form the third alphabet of life, joining the ranks of nucleotides and amino acids, and will also become aware of the importance of cellular communication via glycan-lectin recognition.
Gesehen am 12.02.2020